Wycena transakcji wewnątrzwspólnotowego nabycia i dostawy towarów oraz importu i eksportu towarów - Rudnicka, Bożena (Valuing Transactions of Intra-Community Purchase and Supply, Export and Import of Goods-Issues, 2005)
Principles of valuing transactions of intra-Community purchase and supply, export and import of goods are set forth in few legal acts such as the Accounting Act, the Goods and Services Tax Act, the Income Tax Act. The business practice faces ambiguous definitions and divergent acts in some aspects of the valuation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 91-96